A TOOLBOX DESIGN FOR LABORATORY APPLICATION OF ELECTRONIC NOSE USING VIRTUAL INSTRUMENTATION - Khan, Mohammad Ayub; Chandra, Prakash; Mishra , Pratibha; Sinha, Rajansh (International Journal of Engineering Technologies and Management Research, 2018)
The tool consists of several virtual instrumentation allowing the implantation of the different measurement technique that are commonly used in this research field. What follows describes an integrated system that automatically controls the composition of the mixture under analysis, provides set up for both the virtual instrumentation and customs electronics, and performs the selected class algorithms for features extraction, data dimensionality reduction and classification. Assisting perspective task to virtual instrumentation controlling the entire system gives us the possibility to avoid the presence of error due to human control. Such systems, and in particular those designed for research application, utilize a large number of sub system for chemical sampling control, for signal generation and acquisition, and for data manipulation. This paper describes a tool box of virtual instrumentation developed for research purposes and based on a laboratory electronics nose.